2014
DOI: 10.1093/jac/dku136
|View full text |Cite
|
Sign up to set email alerts
|

The pyrazinamide susceptibility breakpoint above which combination therapy fails

Abstract: ObjectivesTo identify the pyrazinamide MIC above which standard combination therapy fails.MethodsMICs of pyrazinamide were determined for Mycobacterium tuberculosis isolates, cultured from 58 patients in a previous randomized clinical trial in Cape Town, South Africa. The MICs were determined using BACTEC MGIT 960 for isolates that were collected before standard treatment with isoniazid, rifampicin, pyrazinamide and ethambutol commenced. Weekly sputum collections were subsequently made for 8 weeks in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 25 publications
1
57
0
Order By: Relevance
“…Confirmation of these lower critical concentrations have come from clinical studies [209][210][211][212][213] and several investigations [214][215][216][217][218][219][220][221] of drug resistance-associated mutations in isolates with MICs below the standard breakpoint. Clinical studies using assumption-free methods such as machine learning have confirmed that these values (table 3) are in fact the MICs above which tuberculosis patients fail combination therapy.…”
Section: Rv1910cmentioning
confidence: 91%
See 2 more Smart Citations
“…Confirmation of these lower critical concentrations have come from clinical studies [209][210][211][212][213] and several investigations [214][215][216][217][218][219][220][221] of drug resistance-associated mutations in isolates with MICs below the standard breakpoint. Clinical studies using assumption-free methods such as machine learning have confirmed that these values (table 3) are in fact the MICs above which tuberculosis patients fail combination therapy.…”
Section: Rv1910cmentioning
confidence: 91%
“…208 The problem with this definition is logical and mathematical: what do the parameters of the Gaussian curve of the MIC distribution have to do with how well a patient will respond to therapy? 209 Wild-type MIC distributions of any organism vary between regions because of local evolutionary drivers, so it in unclear which to use. 210 The idea that all wild-type distributions are the same is assumed in general microbiology-but they aren't the same, and data show that M tuberculosis is no exception.…”
Section: The Role Of Efflux Pumps In Antibiotic Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…In a recent report, an MIC of Ͼ50 g/ml and Ͻ100 g/ml was associated with a poor 2 month sputum conversion (relative risk of 1.5 [95% confidence interval, 1.2 to 1.8]) compared with that of an MIC of Յ50 g/ml (23). Accordingly, the authors concluded that a PZA susceptibility breakpoint of ϳ50 g/ml should be used for clinical decision making.…”
mentioning
confidence: 99%
“…Accordingly, the authors concluded that a PZA susceptibility breakpoint of ϳ50 g/ml should be used for clinical decision making. However, one cannot exclude other factors that may have contributed to the observed delayed treatment response (23).…”
mentioning
confidence: 99%